Effect of recovery mode on postexercise vagal reactivation in elite synchronized swimmers - Schaal, K.; Le Meur, Y.; Bieuzen, F.; Petit, O.; Hellard, P.; Toussaint, J.-F.; Hausswirth, C. (Applied Physiology, Nutrition, and Metabolism, 2013)
This study investigated the effect of whole-body cryostimulation (WBC), contrast-water therapy (CWT), active recovery (ACT), and passive condition (PAS) protocols on the parasympathetic reactivation and metabolic parameters of recovery in elite synchronized swimmers who performed 2 simulated competition ballets (B1 and B2) separated by 70 min. After determining maximal oxygen consumption (VO2max400) and blood lactate concentrations ([La-]b400) during a 400-m swim trial, 11 swimmers performed 1 protocol per week in randomized order. Heart rate variability (HRV) was measured at rest (PreB1), 5 min after B1 (PostB1), before B2 (PreB2), and 5 min after B2 (PostB2). VO2peak was measured at PostB1 and PostB2, and [La-]b was measured at PostB1, PreB2, and PostB2. PostB1 VO2peak and VO2max400 were similar, but PostB1 [La-]b was higher than [La-]b400 (p = 0.004). Each ballet caused significant decreases in HRV indices. At PreB2, all HRV indices had returned to PreB1 levels in the CWT, PAS, and ACT protocols, whereas the WBC protocol yielded a 2- to 4-fold increase in vagal-related HRV indices, compared with PreB1. WBC and ACT both increased [La-]b recovery, compared with PAS (p = 0.06 and p = 0.04, respectively), and yielded an increased VO2peak from B1 to B2; however, it decreased after PAS (+5.4%, +3.4%, and -3.6%; p < 0.01). This study describes the physiological response to repeated maximal work bouts that are highly specific to elite synchronized swimming. In the context of short-term recovery, WBC yields a strong parasympathetic reactivation, and shows similar effectiveness to ACT on the metabolic parameters of recovery and subsequent exercise capacity.